2013
DOI: 10.7860/jcdr/2013/6060.3207
|View full text |Cite
|
Sign up to set email alerts
|

The M orphometric Analysis of the Mental Foramen in Adult Dry Human Mandibles : A Study on the South Indian Population

Abstract: The knowledge on the variations in the position and size of the mental foramen and the presence of the accessory foramen may be of much use to dental surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…All subjects in this study were of Iranian origin and therefore represented a very ethnically homogenous group. Evaluation of the location of the mental foramen regarding the mandibular posterior teeth in this study showed that the most common types of mental foramens were Type 1 (which was located below the apex of the second premolar) (50.31%) and Type 2 (which was located between the apices of the first and second premolars) (33%) and were in agreement with the results of Singh and Srivastav,[10] Genu et al .,[13] Pokhrel and Bhatnagar et al .,[14] Fujita and Suzuki,[15] Afkhami et al .,[16] Udhaya et al .,[17] Adejuwon et al .,[18] and Yesilyurt et al . 's[19] studies on different ethnic populations.…”
Section: Discussionsupporting
confidence: 88%
“…All subjects in this study were of Iranian origin and therefore represented a very ethnically homogenous group. Evaluation of the location of the mental foramen regarding the mandibular posterior teeth in this study showed that the most common types of mental foramens were Type 1 (which was located below the apex of the second premolar) (50.31%) and Type 2 (which was located between the apices of the first and second premolars) (33%) and were in agreement with the results of Singh and Srivastav,[10] Genu et al .,[13] Pokhrel and Bhatnagar et al .,[14] Fujita and Suzuki,[15] Afkhami et al .,[16] Udhaya et al .,[17] Adejuwon et al .,[18] and Yesilyurt et al . 's[19] studies on different ethnic populations.…”
Section: Discussionsupporting
confidence: 88%
“…Gender, mandibular side, MF anteroposterior position, and the presence of AMF largely determine variations in MF area and MF diameter. Although there are several studies analyzing MF size [ 15 , 16 ], to the best of our knowledge, this is the first study to evaluate whether MF size is influenced by local and general factors using regression model analysis. Previous studies have carried out only a comparative study by age and gender [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies analyzing MF size [ 15 , 16 ], to the best of our knowledge, this is the first study to evaluate whether MF size is influenced by local and general factors using regression model analysis. Previous studies have carried out only a comparative study by age and gender [ 16 19 ]. Regarding general factors, in a CT study Fujita et al [ 20 ] reported no differences in MF dimensions between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on accessory mental foramina are available in the literature, but most of them were conducted on dry mandibles. 1 , 15 Sawyer et al 1 conducted an anthropological study on different ethnic groups and observed an accessory mental foramen frequency of 1.5% to 12.5%, with no clear predilection for gender or age. In general, only one accessory mental foramen is observed in a hemimandible, although the presence of three such foramina has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In general, only one accessory mental foramen is observed in a hemimandible, although the presence of three such foramina has also been reported. 1 , 15 Clinical and radiographic studies of this condition are less frequent, 10 and an even smaller proportion of cases involve CT and CBCT. 3 , 4 , 5 , 12 , 13 , 16 …”
Section: Discussionmentioning
confidence: 99%